Recent progresses of simulations on passive membrane permeations in China. Issue 10 (2nd July 2016) - Zhang, Hui-Yuan; Xu, Qin; Li, Fang; Tian, Pei-Chuan; Wang, Ying-Hao; Xiong, Yi; Zhang, Yong-Hong; Wei, Dong-Qing
Abstract: Membranes are vital for many cellular processes, providing compartments in living organism as well as specific/non-specific permeation pathways through them. These pathways may be transiently formed tunnels in the lipid bilayers, stable membrane pores or highly specific protein channels, which may all have their special selectivities for different solutes. Understandings in the mechanisms of transmembrane permeations through these different pathways are important in development of drug delivery systems, structure-based drug design and various medical strategies. In this article, we reviewed recent progress in China of computational simulations on the cross-membrane passive permeations, including direct permeations through lipid bilayers, passive diffusion through membrane pores and facilitated diffusions through highly selective channels. The illustrated papers cover the cross-membrane permeations of ions-like charged groups, the insertion of antimicrobial peptides, the membrane pore of peptidal oligomers, the blockage and control of selectivities of membrane channel as well as voltage and ligand gating. These computational simulations may provide further understandings on membrane permeations and the function of membrane proteins, as well as possible new ideas for drug design.